Measuring educational neglect using the Q method: A model based on the burden of disseminated tungiasis - Martins, Ana Carolina Tardin; Martins, Luciana Pereira Freire; Timbó, Renata Velozo; Bezerra, Natanael Victor Furtunato; Urdapilleta, Ada Amalia Ayala; Filho, Florival Martins Passos; Gomes, Ciro Martins (Frontiers in Epidemiology, 2022)
Background: A paramount factor in the control of neglected tropical diseases from both medical and social aspects is education. New strategies must be constantly pursued to test and provide educational information related to diseases affecting vulnerable populations. We applied the Q method as a model to measure educational neglect based on the burden of disseminated tungiasis. Methods: Using a saturation method for sample size calculation, we recruited students and healthcare professionals to evaluate and classify 27 statements related to the prevention, control and treatment of tungiasis. After quantitative analysis, the Q method was applied based on the paired use of the centroid method and Varimax rotation, and 4 factors were extracted representing the main sets of viewpoints among the participants. Results: We included 119 healthcare professionals with different academic degrees. Statements classified by specialists with a + agreement were also classified as a + agreement by most of the participants. However, we detected 5 important disagreements related to the topical treatment of tungiasis and control of the disease in the environment and animals. The Q method showed that almost no consensus was detected for four statements. The classification of each statement was not related to the participants’ academic degree. Conclusions: There is significant educational neglect related to tungiasis prevention and treatment in healthcare sciences in Brazil. We conclude that the Q method may be an interesting strategy alone or associated with quantitative strategies for detecting educational limitations related to neglected diseases. In countries where neglected diseases are endemic, a detailed study evaluating the quality of education related to these diseases must be prioritized.